Tibetan Refugee Journeys: Representations of Escape and Transit - Rebecca Frilund (OXFORD UNIV PRESS, 2022)
This ethnographic study contributes to the scholarly call to increase studies on refugee journeys. It explores Tibetan journeys via Nepal to India and provides a novel case study about the Tibetan refugees who commonly cross the Himalayas at least partly on foot without passports and head to the Tibetan Reception Centre in Kathmandu, Nepal, from where they are assisted to India. Conceptually, the study argues that combining the studies of refugee journeys and transit migration increases understanding of the (Tibetan) refugee journeys. The findings reveal that the risky journey has a remarkable meaning both for those Tibetans who have done the journey and collectively for the diaspora Tibetans in India. As Tibetans, like refugees in general are still often victimised and their subjectivities overlooked, the study also contributes to a fuller understanding of the Tibetan refugee agency through the journey narratives of the interviewees of this study.